Do Rural Longitudinal Integrated Clerkships Impact Choice of Residency Type and/or Permanent Community Practice in Surgery? - Bennett J. Maki (University of Minnesota Libraries Publishing, 2021)
Purpose: Rural general surgery experiences during medical school appear to have influenced the decision of prospective general surgery applicants to pursue residency programs that provide rural surgery opportunities. This is an analysis of a single cohort, rural-focused, longitudinal integrated clerkship to determine if there is an association between type of residency program and completion of a rural-focused longitudinal integrated clerkship.